Conversational speech levels and signal-to-noise ratios in realistic acoustic conditions - Weisser, Adam; Buchholz, Jörg M. (The Journal of the Acoustical Society of America, 2019)
Estimating the basic acoustic parameters of conversational speech in noisy real-world conditions has been an elusive task in hearing research. Nevertheless, these data are essential ingredients for speech intelligibility tests and fitting rules for hearing aids. Previous surveys did not provide clear methodology for their acoustic measurements and setups, were opaque about their samples, or did not control for distance between the talker and listener, even though people are known to adapt their distance in noisy conversations. In the present study, conversations were elicited between pairs of people by asking them to play a collaborative game that required them to communicate. While performing this task, the subjects listened to binaural recordings of different everyday scenes, which were presented to them at their original sound pressure level (SPL) via highly open headphones. Their voices were recorded separately using calibrated headset microphones. The subjects were seated inside an anechoic chamber at 1 and 0.5 m distances. Precise estimates of realistic speech levels and signal-to-noise ratios (SNRs) were obtained for the different acoustic scenes, at broadband and third octave levels. It is shown that with acoustic background noise at above approximately 69 dB SPL at 1 m distance, or 75 dB SPL at 0.5 m, the average SNR can become negative. It is shown through interpolation of the two conditions that if the conversation partners would have been allowed to optimize their positions by moving closer to each other, then positive SNRs should be only observed above 75 dB SPL. The implications of the results on speech tests and hearing aid fitting rules are discussed.